Effects of different concentrations of sucrose and citric acid on vase life of rose - Aryal, Pragya; Adhikari, Anjila; Pathak, Rukmangat; Pudasaini, Rameshwor (Journal of Agriculture and Natural Resources, 2019)
Vase life is the most important parameter to determine the quality of cut flower, however, due to highly perishable nature is always challenging to vase life. An experiment was conducted at Horticulture Lab, Prithu Technical College, Dangon 2018 in order to find out best concentration of sucrose and citric solution that enhances and prolongs the better flower quality and longevity. Experiment was laid out in completely randomize design (CRD) with nine treatments and three replication. Rose sticks were harvested at flower bud stage and two sticks were kept in each vase solution. 2% sucrose with 15 ppm citric acid solution found longest vase life and this combination has the potential to be used as a commercial cut flower preservative solution to delay flower senescence, enhance post-harvest quality and prolong the vase life of cut rose flowers.